PERILAKU PENGRAJIN GULA MERAH TEBU TRADISIONAL DI NAGARI BUKIK BATABUAH, KECAMATAN CANDUANG, KABUPATEN AGAM - Ivonne Ayesha; Yurnalis Yurnalis; Mukhnizar Mukhnizar (Jurnal Pembangunan Nagari, 2016)
The objectives of this study was to evaluate, to understand and to analysis production behavior comonted by the farmers as brown sugar cane producer in the Nagari Bukik Batabuah, the sub-district of Canduang, the district oh Agam. Site of the location being studied was determined purposively based on such a determination that this village was one of brown sugar cane production centre which is famous in West sumatera, and known as one of the local specific product in Ranah Minang. Aqualitative design was applied in this case study. The respondents is farmers who produce brown sugar cane. The results of this study indicated that those farmers-brown sugar cane producers had a unique behavior in their business. Their decisios to produce brown sugar cane was depend upon their household requirement upon money income. By those reasons, the farmers-brown sugar cane producers will produce more if the price of this product was relatively low. On the contracy, the will reduce their product wherever the price of brown sugar cane was getting higher. These farmers decision in producing brown sugar cane was imfact not determined by the market demand, si that maximum production was not occur at the high in case of its demand. Conversely, the minimum production was also not occur during its demand decrease.